Quadradinhos e a visualidade multissensorial - Brigido, Marcelo Figueira (2021)
Submitted by Susana Santos (susana.santos@universidadeeuropeia.pt) on 2021-04-22T16:20:26Z No. of bitstreams: 2 MA_Design e Cultura Visual CAPA.pdf: 353905 bytes, checksum: 3210d51e287cc04369bde064417d89b2 (MD5) Marcelo_Brigido_Tese.pdf: 5077278 bytes, checksum: 697265e3b527d49e816f97ba54b93763 (MD5)